2013
DOI: 10.1080/17470919.2013.870091
|View full text |Cite
|
Sign up to set email alerts
|

Affective basis of judgment-behavior discrepancy in virtual experiences of moral dilemmas

Abstract: Although research in moral psychology in the last decade has relied heavily on hypothetical moral dilemmas and has been effective in understanding moral judgment, how these judgments translate into behaviors remains a largely unexplored issue due to the harmful nature of the acts involved. To study this link, we follow a new approach based on a desktop virtual reality environment. In our within-subjects experiment, participants exhibited an order-dependent judgment-behavior discrepancy across temporally separa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
134
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 165 publications
(154 citation statements)
references
References 32 publications
(52 reference statements)
17
134
1
2
Order By: Relevance
“…over appropriateness of action ("Is it appropriate for you to do it?") because: (i) it tends to be more emotionally arousing 102 , (ii) it tends to elicit more egocentric/self-focused (versus allocentric/other-focused) frame of reference because of potential self-relevant consequences 103 , and (iii) perceived appropriateness of utilitarian course of action on moral dilemmas does not differ in ASD 11 (as compared to healthy controls). Thus, the behavioural choice of action provides a more sensitive measure to tap into moral cognition in autism.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…over appropriateness of action ("Is it appropriate for you to do it?") because: (i) it tends to be more emotionally arousing 102 , (ii) it tends to elicit more egocentric/self-focused (versus allocentric/other-focused) frame of reference because of potential self-relevant consequences 103 , and (iii) perceived appropriateness of utilitarian course of action on moral dilemmas does not differ in ASD 11 (as compared to healthy controls). Thus, the behavioural choice of action provides a more sensitive measure to tap into moral cognition in autism.…”
Section: Methodsmentioning
confidence: 99%
“…and found that alexithymia was predictive of acceptability judgments only in controls but not in ASD and concluded that autistics' judgments were based on complying with social rules and were less susceptible to emotional biases. It is possible that these differences stem from emotional saliency of the stimuli used across studies; moral dilemmas involve situations where the individuals have to mull over behavioural choice of directly harming or even killing someone for the benefit of the many and are, thus, inherently highly emotionally evocative 49 , while providing more objective acceptability judgments about emotional sentences may not engage emotional processes to the same extent 102,103 . Another possibility is that there was not enough variation in alexithymia scores in their ASD group to detect an effect (indeed, variance in alexithymia scores in the control group was higher than in the ASD group in the previous study 6 ).…”
Section: Dissociable Empathy-utilitarianism Associations Between Autimentioning
confidence: 99%
“…In short, our project sought to interrogate and prioritize the physicality of the footbridge dilemma. While previous research had attempted to depart from theoretical instances of these moral dilemmas by generating visually salient scenarios using virtual reality (VR; see Figure 2; e.g., Francis et al, 2016;Patil, Cogoni, Zangrando, Chittaro, & Silani, 2014), this research has yet to consider the significance of physical salience in moral dilemmas; what would happen if making a moral decision felt real? 6 This is where a practice-based methodology can offer insights.…”
Section: Dilemmas Of Morality and Measurementmentioning
confidence: 99%
“…Firstly, the mechanics of the sculpture were designed for interaction, allowing the sculpture to replace typical testing tools such as joystick controllers (Francis et al, 2016;Patil et al, 2014). Secondly, aesthetic realism and tactile sensation were simulated through expandable foam and platinum grade silicone.…”
Section: Distorted Dimensionsmentioning
confidence: 99%
“…The design of the sculpture or testing tool, which was the focal point of Distorted Dimensions, pivoted around three central aims. Firstly, the mechanics of the sculpture were designed for interaction, allowing the sculpture to replace typical testing tools such as joystick controllers (Francis et al, 2016;Patil et al, 2014). Secondly, aesthetic realism and tactile sensation were simulated through expandable foam and platinum grade silicone.…”
Section: Distorted Dimensionsmentioning
confidence: 99%